2011
DOI: 10.1007/s00253-011-3353-9
|View full text |Cite
|
Sign up to set email alerts
|

A sirA-like gene, sirA2, is essential for 3-succinoyl-pyridine metabolism in the newly isolated nicotine-degrading Pseudomonas sp. HZN6 strain

Abstract: A novel nicotine-degrading Pseudomonas sp. strain, HZN6, was isolated from a pesticide-wastewater treatment facility in Hangzhou. The strain could grow on nicotine as its sole source of carbon, nitrogen, and energy. The strain's main intermediate metabolites were determined to be pseudooxynicotine, 3-succinoyl-pyridine (SP), and 6-hydroxy-3-succinoyl-pyridine (HSP). A Tn5 transposon mutant was generated in which the degradation pathway was blocked at the SP. A 4,583-bp DNA fragment flanking the transposon inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…The degradation mechanism of nicotine in Pseudomonas has been studied for more than 50 years (21,28). However, there have been few studies at the genetic level reported so far.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The degradation mechanism of nicotine in Pseudomonas has been studied for more than 50 years (21,28). However, there have been few studies at the genetic level reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…The in-frame disruption of the pao and sap genes in Pseudomonas sp. strain HZN6 was performed using suicide plasmid pJQ200SK and a twostep homologous recombination method, as described previously (21). Briefly, to disrupt the pao gene, a 1.749-kb fusion product was constructed by PCR, which consisted of an upstream sequence of the pao gene, kanamycin resistance gene, and downstream sequence using primers paoUFBamHI/paoUR, KmF/KmR, and paoDF/paoDR-SpeI (see Table S1 in the supplemental material), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations